2012
DOI: 10.7837/kosomes.2012.18.6.557
|View full text |Cite
|
Sign up to set email alerts
|

Method on the Effective Onboard Training and Guidance for Apprentice Engineer Officers in the Training Ship - The Case of Mokpo National Maritime University -

Abstract: The aim of onboard training of apprentice engineers in the training ship is to support and enhance fundamental knowledge and ability to have both theoretical and practical skills. This diversity in education and training improve the capability to handle problems in a crisis and build-up the feeling of confidence so they can effectively accomplish their assigned tasks in special circumstance like those onboard. Therefore this study suggests some remedies for qualitative improvement and guidance of onboard train… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In Maritime Education and Training (MET), enhancing ship operators' maneuvering ability has been the primary purpose of training [1,2] because it is strongly related to maritime accidents [3]. At present, on-scene training is obligatory for trainees [4,5], although opportunities to maneuver a ship as a cadet in situations that require attention are somewhat limited for rational reasons for safety [6]. Instead, simulation training (ST) is performed for safety and repeatability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In Maritime Education and Training (MET), enhancing ship operators' maneuvering ability has been the primary purpose of training [1,2] because it is strongly related to maritime accidents [3]. At present, on-scene training is obligatory for trainees [4,5], although opportunities to maneuver a ship as a cadet in situations that require attention are somewhat limited for rational reasons for safety [6]. Instead, simulation training (ST) is performed for safety and repeatability [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The International Maritime Organization (IMO) established the International Convention on Standards of Training, Certification, and Watchkeeping for Seafarers (STCW) in 1978 to set mandatory minimum requirements for the certification of seafarers [4]. As per Chapter II (Standards regarding the Master and Deck Department) and Chapter III (Standards regarding the Engine Department) of the STCW, cadets should complete onboard training to achieve a certificate of competency [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted regarding the improvement of onboard training environments. In terms of the effectiveness of onboard training, an effective training program can be formulated if onboard training is taken seriously [14] and a realistic curriculum is created that includes legal inspections of ships during the semester and practicing the use of various types of equipment [4]. Sin and Im [15] examined differences in cadets' satisfaction with their onboard training on shipping companies' ships and universities' training ships in the categories of consciousness, education, and environment, and found that shipping companies need to offer more systematic education to cadets and that universities need to improve education environments by paying attention to living environments and food quality.…”
Section: Introductionmentioning
confidence: 99%